Quality of life assessment of children with thalassemia - Masyitah Sri Wahyuni; Muhammad Ali; Nelly Rosdiana; Bidasari Lubis (Indonesian Pediatric Society Publishing House, 2011)
Background Thalassemia is a chronic disease that is becoming a major health problem in the world, including the Mediterranean, as well as Malaysia, Thailand and Indonesia. This condition clearly affects the patient's quality of life, because of the condition itself and the effects of treatment. Assessment is needed to detennine actions to be taken to improve the quality of life in thalassemic children. Objective To assess the differences in quality of life of thalassemic children compared to their normal siblings. Methods We perfonned a cross􀁌sectional study from May 2010 until June 2010 in H. Adam Malik Hospital, Medan and the home of a member of the North Sumatra Chapter of the Association of Parents of Thalassemia Sufferers (perhimpunan Orangtua Penderita Talasemia Indonesia, POPTI). Thalassemic children aged 5-18 years and their age and gender􀁌adjusted siblings were divided into two groups: case group and control group. Parents and children were asked to fill the PedsQL (Pediatric Quality of life Inventory) version 4.0 questionnaire to assess their quality of life. Results There were 59 children in each group. The assessments of four quality of life domains in the thalassemic group vs the control group showed the folloMng: physical function 53.1 vs 71.5 (95% CI -21.41 to -15.26, P􀁍O.OOOI), emotional function 50.9 vs 62.9 (95% CI -16.82 to -7 .41, P􀁍O.OOO 1), social function 62.5 vs 72.8 (95% CI-13.50 to -7.01, P􀁍O.OOOI) and school function 36.2 vs 56.0 (95% CI -22.95 to -16.71, P􀁍O.OOOI). Total scores were 50.9 vs 66.1 (95% CI -18.20to -13.12, P􀁍O.OOOI). School function was the most affected parameter studied, with thalassemic children scoring lower than the control group. Conclusion There were significant decreases in the quality of life parameters in the thalassemic group compared to the control group. Thalassemic children have poorer quality oflife compared to their nonnal siblings, Mth school function being the most affected domain.